Peranan Wanita dalam Menunjang Ekonomi Keluarga di Kecamatan Batu Bangga Kabupaten Kolaka - Taufiq, Muhammad (Jurnal Aplikasi Manajemen, 2008)
The study aims to find out women's role in supporting their family's economy at Batu Bangga Sub District, Kolaka Regency. Data were collected through interviews and literary study. Data were then analyzed descriptively and presented through tabulations and x2 analysis. The results showed that economically active housewives had more economic activities (63,64%) bearing 3-4 people. While, economically in-active housewives, most of them had many more people under their responsibility (66,67%) of five or more. This indicated that there was close relationship between people under responsibility with the levels of their involvement in various economic activities. As proved by the chi-square count of 19.867 larger that chi square table with freedom degree 4 and 0.05 significant level of 9.488.